ADAPTIVE STRATEGIES OF DAWEA BATIK (BONDOWOSO) IN RESPONSE TO DECLINING INSTITUTIONAL DEMAND AND ITS IMPLICATIONS FOR CONSUMER PURCHASING DECISIONS: A SINGLE-CASE STUDY - Ita Marianingsih; M. Ilham Zainullah; Novita Purnamasari (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2026)
This study examines how Dawea Batik MSME adapts to declining institutional demand particularly demand related to organizational/uniform procurement and how these adaptive actions relate to consumers’ purchasing decisions. Using a qualitative single-case study design, primary data were collected through in-depth interviews with key actors (owner/manager, workers, and consumers) and supported by observation and relevant documents. Data were analyzed thematically through coding, with validity strengthened via source triangulation and member checking. The findings indicate three main adaptive strategies: (1) product innovation and diversification (2) enhancement of digital marketing channels (e.g., Instagram, TikTok, WhatsApp), and (3) strengthening cultural tourism education through live batik workshop programs. These strategies are associated with consumer decision-making across stages of problem recognition, information search, evaluation, purchase, and post-purchase behavior (Kotler, 2009), mainly by increasing consumer engagement, perceived value, and trust. As a single-case study, the findings offer analytic insights for similar creative-industry MSMEs while acknowledging limited statistical generalization.